(untitled) (Journal of the Bangladesh Agricultural University, 2010)
A variation of the Almost Ideal Demand System (AIDS) model of Deaton and Muellbauer (1980) has been employed to determine the impacts of per capita total expenditure, food prices and demographic variables on household demand for dairy products in Bangladesh. The budget shares are generally more responsive to per capita total expenditure than to prices. With respect to demographic effects, it is found that family size and occupation of the household head have a statistically significant impact on household demand behavior. Key words: Household, Demand; Dairy Products; AIDS; Elasticity DOI: 10.3329/jbau.v8i1.6408 J. Bangladesh Agril. Univ. 8(1): 121-126, 2010